Ocean Advocacy in Discourse: Unpacking 'Seaspiracy' through an Eco-Critical Lens - Putrianti Viola Novitasari; Galuh Nur Rohmah (Universitas Al Azhar Indonesia, 2023)
The decrease in the wildlife population over the last 30 years was caused by various human actions, one of them was triggered by various writings and discourses spread in society. This study aims to analyze the narration of documentary film